Abdominal pseudo hernia: a rare sequelae of complicated herpes zoster - Vethanayagam, Mohankumar; S, Senthilkumar.; C., Subha K.; Rajagopalan, Rajesh; R., Bhaskaran. (International Journal of Advances in Medicine, 2017)
Herpes zoster (HZ) caused by Varicella Zoster Virus causes several complications, the most common being PHN (Post Herpetic Neuralgia). Here we report a case of phantom hernia following HZ involving T10-T11 dermatome. Close follow up will ensure full recovery to avoid unnecessary surgical intervention.